2008
DOI: 10.1016/j.ejcts.2007.12.036
|View full text |Cite
|
Sign up to set email alerts
|

The optimal technique for combined application of fibrin sealant and bioabsorbable felt against alveolar air leakage☆☆☆

Abstract: The novel Rub+Soak B technique was the most effective and reasonable combination technique wherein the sealing mechanism was supported by the physical properties of the fibrin sealant components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…The Beriplast P® Combi-Set consists of two separate vials that contain individual reagents (fibrinogen solution and thrombin solution), which form a fibrin clot upon being combined. Itano et al examined five different combination procedures with PGA felt and fibrin sealant to cover pleural defects in lungs from swine and reported that a specific method in which PGA felt was soaked in thrombin solution and applied to the coagulated surface after spraying fibrinogen liquid on the surface was the most effective method for sealing pleural defects [32]. In our current series, we employed this method for pancreatic remnant closure.…”
Section: Discussionmentioning
confidence: 90%
“…The Beriplast P® Combi-Set consists of two separate vials that contain individual reagents (fibrinogen solution and thrombin solution), which form a fibrin clot upon being combined. Itano et al examined five different combination procedures with PGA felt and fibrin sealant to cover pleural defects in lungs from swine and reported that a specific method in which PGA felt was soaked in thrombin solution and applied to the coagulated surface after spraying fibrinogen liquid on the surface was the most effective method for sealing pleural defects [32]. In our current series, we employed this method for pancreatic remnant closure.…”
Section: Discussionmentioning
confidence: 90%
“…Although there have been many reports concerning the efficacy of absorbable mesh and fibrin glue for reducing air leakage from surgical margins [13,14,16,17], there is no evidence that absorbable mesh and fibrin glue thickens and reinforces normal pleura. Most experimental data were about the effectiveness of a mesh and glue for artificial pleural defects or injuries [16,18].…”
Section: Discussionmentioning
confidence: 97%
“…Most experimental data were about the effectiveness of a mesh and glue for artificial pleural defects or injuries [16,18]. We understand that fibrin glue promotes the coagulation cascade and healing reaction at the surgical pleural margin injured by stapling instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous application by spraying created a strong sealant that could bear high pressure (above 220 mm Hg), whereas separate application resulted in weaker sealing. Several application techniques have been compared for application in cases of alveolar air leakage [ 15 ] .…”
Section: Fibrin Glue In Combination With Pga Sheet (Neoveil)mentioning
confidence: 99%